ANALISIS BIAYA DAN WAKTU MENGGUNAKAN TIME COST TRADE OFF (TCTO) DALAM RANGKA MENGEJAR WAKTU PELAKSANAAN (Studi Kasus: Proyek Pembangunan Rumah Sakit Islam Jakarta Pondok Kopi) - Thesa Nurshela; Nikko Rozy (JURNAL TEKNIK SIPIL CENDEKIA (JTSC), 2026)
In a construction project, there are three crucial aspects to consider, namely time, cost, and quality. The implementation of the Jakarta Islamic Hospital Pondok Kopi construction project faces several obstacles, especially at the stage of foundation structure and concrete structure work. Based on observations at the location, it is estimated that the completion of the construction of the Jakarta Islamic Hospital Pondok Kopi will be delayed or not in accordance with the planned schedule. There are several options that can be used to speed up project activities, including increasing working hours (overtime), adding manpower, adding or changing tools, adding more effective work methods, and other options. Of the several available alternatives, this study will apply two alternatives, namely increasing working hours (overtime) and increasing labor using the Time Cost Trade Off (TCTO) method. The optimization alternative that has the most optimal or efficient total cost and duration is by adding 5 workers because the project duration becomes faster, even though there is an increase in cost, the addition is more optimal or efficient compared to other alternatives, as indicated by a time efficiency of 51,36% and a cost efficiency of -20,02%. This optimization result can be used as an acceleration option for the project party.